Lost boys of Sudan - Mylan, Megan; Shenk, Jon.; Chuor, Santino Majok; Dut, Peter Nyarol; Actual Films; Principe Productions; P.O.V. (Firm) ([United States] : New Video Group : Docurama, 2004)
The journey of two teenage Sudanese boys, orphaned by their war torn country, who traveled to America looking for a safer environment and learning to cope with the unfamiliar complexities of contemporary American society.
DVD.
Santino Majok Chuor, Peter Nyarol Dut.
Cinematographer, Jon Shenk.
Originally released as a documentary feature in 2003.
Closed-Captioned
Keywords: Chuor, Santino Majok; Dut, Peter Nyarol; Sudanese -- United States; Sudanese -- Cultural assimilation -- United States; Children and war -- Sudan; Video recordings for hard of hearing people; Documentary films